Independence from the perspective of Shari’ah Committee - Zainal Abidin, Nor Hafizah; Mat Yasin, Fatimah; Zainal Abidin, Ahmad (2019)
Being a gatekeeper of Shari’ah compliance and to hold responsibilities to mitigate Shari’ah non-compliance risks are among the main roles of Shari’ah Committee. Shari’ah Committee experience challenges that may adversely affect their responsibilities to discharge effective oversight duties. Hence, an effective Shari’ah Committee would require certain degree of independence. The purpose of the study is to gather perceptions of Shari’ah Committee on factors that construct or impair their independence in performing their oversight duties. Data were gathered through semi-structured interviews that were conducted with twelve Shari’ah Committee. Results, as perceived by Shari’ah Committee, indicated that independence within the context of Shari’ah Committee were constructed on the basis of competence, attitude of Shari’ah committee and accountability. Apart from that, reliance on financial remuneration and cross or multiple appointments may impair their independence. Thus, insights from this study underlines other fit and proper criteria that need to be considered in ensuring Shari’ah Committee are able to deliver their roles and responsibilities independently given its specific context.